Bourdieu and the Cult of the Saints as Cultural Theology - Eastman, David L. (Religion & theology, 2025)
Despite advancements by social historians in early Christian studies, the narrative remains heavily influenced by the writings of bishops and theologians. Practices of non-elites are often dismissed as "popular religion," implicitly contrasting them with "proper" theology. This paper employs Pierre Bourdieu’s habitus to analyze patron-client dynamics within the early Christian cult of the saints. Such an approach discursively reorients scholarly descriptions away from the pejorative "popular religion" toward a new nomenclature that I am proposing, "cultural theology," which more accurately reflects these practices as integral to the period’s working theology and cultural milieu.